Exceptional nitrogen-resorption efficiency enables Maireana species (Chenopodiaceae) to function as pioneers at a mine-restoration site - Zhong, H.; Zhou, J.; Wong, Wei-San; Cross, Adam; Lambers, Hans (2021)
Tailings are among the most challenging mined substrates for plant re-establishment, in particular because of a lack of soil-like structure and nitrogen. Potential pioneer plants are sometimes found in such disturbed and infertile sites. We present a group of pioneer species from the genus Maireana (Chenopodiaceae) that are promising candidates for the restoration of magnetite tailings. We found that these Maireana species did not rely on biologically fixed N from the atmosphere, but exhibited an exceptionally high leaf N-resorption efficiency (about 95%) during leaf senescence, at the same time effectively scavenging trace amount of N from the substrate, in part through rapid transpiration.